Sources of Income Persistence: Evidence from Rural El Salvador - Walter Sosa-Escudero; Mariana Marchionni; Omar Arias (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2006)
This paper uses a unique panel dataset (1995-2001) of rural El Salvador to investigate the main sources of the persistence and variability of incomes. First we propose an econometric framework where a general dynamic panel model is validly reduced to a simple linear structure with a dynamic covariance structure, which augments considerably the number of degrees of freedom usually lost in the construction of instruments to estimate standard dynamic panel models. Then we investigate the extent to which families are continuously poor due to endowments (observed and unobserved) that yield low income potential or due to systematic income shocks that they are unable to smooth. We find that life-cycle incomes are largely explained by the relatively time-invariant productive characteristics of families and their members such as education, public goods and other assets. Observed income determinants account for about half of income persistence. Controlling for unobserved heterogeneity leaves little room for pure state dependence. Although of second order, high volatility and the inability to insure from shocks is a more important source of variation in incomes than in developed countries. Low income potential is the more likely source of poverty traps in Rural El Salvador. Many of the family endowments are manipulable by policy interventions, although many not in the short term.
Keywords: I32; 330; Income mobility; Poverty Traps; Panel Data; El Salvador